Faktor-faktor yang mempengaruhi perkembangan keuangan pada LKM Ida Martunas - Purba, Sindi Claudia; Fathimah, Vidya (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to determine the factors that influence the development of Ida Martunas Microfinance Institution (MFI). This research uses qualitative methods that aim to explain a phenomenon in depth and is carried out by collecting data as deeply as possible. The data types used are primary data and secondary data. Secondary data was obtained by conducting a literature review of data obtained from related agencies, while primary data was obtained from interviews at the Ida Martunas Microfinance Institution (MFI). This research focuses on how the Ida Martunas MFI develops and maintains the sustainability of the business being carried out. From the results of the study, it is known that there are several factors that affect the development of microfinance institutions. These factors include the management system of Ida Martunas MFI, human resources, and marketing systems.